PENGUNGKAPAN PERISTIWA SETELAH PERIODE PELAPORAN PADA MASA PANDEMI COVID-19 TERHADAP PERUSAHAAN TELEKOMUNIKASI DI BURSA EFEK INDONESIA TAHUN 2020 - Sintawati, Diana; Meydiana, Dita; Paramitha, Nahda; Yahfis, Wulandari; Putri, Afifa Rizky (Transpublika Publisher, 2022)
The emergence of Covid-19 in Indonesia in 2020 affected the economic conditions of the country and companies from various sectors. This pandemic event could have a material impact on the company's financial statements in 2020 that require adjustments. This study aims to analyze the account of events after the reporting period during the pandemic in the telecommunications sector company in 2020. The research method used is a literature study with the data obtained in the form of secondary data from the financial statements of telecommunications companies listed on the Stock Exchange in 2020. The results reveals that some companies present pandemic events in the event accounts after the reporting period as events that do not need to be adjusted because they do not affect the number of certain accounts in the financial statements results based on research, non-adjusting event pandemic evoked events. These financial events are recorded in the Financial Notes (CALK) as information so that it can be an illustration that the financial statements have reflected the actual conditions.